Assessment of the performance of Y2SiO5-YSZ/YSZ double-layered thermal barrier coatings. Issue 2 (February 2019) - Hao, Wei; Zhang, Qihui; Xing, Chen; Guo, Fangwei; Yi, Meiyu; Zhao, Xiaofeng; Xiao, Ping
Abstract: Y2 SiO5 is a promising material for the thermal barrier coatings due to its low thermal conductivity, high temperature stability and exceptional resistance for molten silicate attack. However, it suffers low fracture toughness and low coefficient of thermal expansion compared with yttria-stabilized zirconia (YSZ). In this study, a composite coating approach, i.e., incorporating YSZ into Y2 SiO5 coating, was employed to overcome those limitations. The double-layered Y2 SiO5 -YSZ/YSZ coatings were fabricated using atomospheric plasma spraying and tested under thermal cycling at 1150 °C. The phase compositions, microstructure, mechanical properties and the failure behavior were evaluated. It was found that the amorphous phase during spraying would crystallize at high temperature accompanied by volume shrinkage, leading to cracks and spallation in the coating. With YSZ addition, the composite coatings exhibited a much longer lifetime than the single phase Y2 SiO5 coating due to a lower volume shrinkage and enhanced toughness.